Public Administration as One of the Forms for Exercising State Power - Serohina, Svitlana Hryhorivna; Mykolenko, Olena Mykolayivna; Seliukov, Vadym; Lialiuk, Oleksii (Jurnal Cita Hukum, 2021)
The problematic issues related to the definition of public administration as one of the forms of exercising state power are considered. The level of how the quality of public administration processes affects the functioning of the state system and its key mechanisms is analyzed. An important emphasis is placed on the fact that the most useful of the successful practices of public administration in developed countries can be adopted for the state system of Ukraine. Modern problems and ways of their effective solution at different levels of state and local administration are actualized. The analysis of the basic structural elements of qualitative public administration, the level of their influence on processes of realization of the state-power powers within functioning of the state system is offered. For example, it explains whether transparency and impartiality do have a significant impact on the efficiency of public administration. The efficiency (effectiveness) of various, "non-traditional" ways and means of realization of public-administrative activity is established. The conclusions of both leading scholars are analyzed, and the author's assessment of the extent to which the adoption of strategies and tactics of management activities borrowed from other areas of socially useful activity are useful for the field of public administration. First of all, this applies to the sphere of private business. After all, the analyzed experience of developed countries proves that Ukraine can borrow a lot of useful solutions and practical effective tools from private industries.Keywords: Public Administration; State Power; Public Administration; Effective Activity Administrasi Negara Sebagai Salah Satu Bentuk Penyelenggaraan Kekuasaan Negara AbstrakIsu-isu problematik terkait dengan definisi administrasi publik sebagai salah satu bentuk pelaksanaan kekuasaan negara yang patut dipertimbangkan. Tingkat bagaimana kualitas proses administrasi publik mempengaruhi fungsi sistem negara dan mekanisme kuncinya dianalisis. Penekanan penting ditempatkan pada fakta bahwa praktik administrasi publik yang paling berguna dan yang berhasil di negara maju dapat diadopsi untuk sistem negara Ukraina. Masalah modern dan cara penyelesaiannya yang efektif di berbagai tingkat administrasi negara bagian dan lokal diaktualisasikan. Analisis elemen-elemen struktural dasar administrasi publik kualitatif, tingkat pengaruhnya terhadap proses realisasi kekuatan-kekuatan negara dalam fungsi sistem negara ditawarkan. Misalnya, menjelaskan apakah transparansi dan ketidakberpihakan memang memiliki dampak signifikan terhadap efisiensi administrasi publik. Efisiensi (efektivitas) dari berbagai, "non-tradisional" cara dan sarana realisasi kegiatan administrasi publik didirikan. Kesimpulan dari kedua cendekiawan terkemuka dianalisis, dan penilaian penulis tentang sejauh mana penerapan strategi dan taktik kegiatan manajemen yang dipinjam dari bidang lain dari kegiatan yang bermanfaat secara sosial berguna untuk bidang administrasi publik. Pertama-tama, ini berlaku untuk bidang bisnis swasta. Bagaimanapun, pengalaman yang dianalisis dari negara-negara maju membuktikan bahwa Ukraina dapat meminjam banyak solusi yang berguna dan alat praktis yang efektif dari industri swasta.Kata kunci: Administrasi Publik; Kekuasaan Negara; Ilmu Pemerintahan; Aktivitas Efektif Государственное управление как одна из форм осуществления государственной власти Аннотация В статье рассматриваются проблемные вопросы, связанные с определением публичного администрирования как одной из форм реализации государственной власти. Проанализирован уровень влияния качества процессов государственного управления на функционирование государственной системы и ее ключевых механизмов. Важный акцент делается на том, что именно полезного из успешных практик функционирования публичного администрирования в развитых странах можно перенять для государственной системы Украины. Актуализируются современные проблемы и пути их эффективного решения на разных уровнях государственного и местного управления. Предлагается анализ основных структурных элементов качественного публичного администрирования, уровень их влияния на процессы реализации государственно-властных полномочий в пределах функционирования государственной системы. Например, объясняется, действительно ли прозрачность и беспристрастность оказывают значительное влияние на эффективность публичного администрирования. Устанавливается эффективность (действенность) различных, «нетрадиционных» способов и средств реализации публично-административной деятельности. Анализируются выводы как ведущих ученых, так и предлагается авторская оценка того, в какой степени для сферы публичного администрирования полезно заимствование стратегий и тактик осуществления управленческой деятельности. Прежде всего это касается сферы частного бизнеса, поскольку опыт развитых стран доказывает, что Украина может позаимствовать немало полезных решений и практически эффективных инструментариев именно из частных отраслей.Ключевые слова: Публичное Администрирование; Государственная Власть; Общественное Управление; Государственная Система